Examining the relationship of immunotherapy and wound complications following flap reconstruction in patients with head and neck cancer. Issue 5 (8th January 2021) - Mays, Ashley C.; Yarlagadda, Bharat; Achim, Virginie; Jackson, Ryan; Pipkorn, Patrik; Huang, Andrew T.; Rajasekaran, Karthik; Sridharan, Shaum; Rosko, Andrew J.; Orosco, Ryan K.; Coughlin, Andrew M.; Wax, Mark K.; et al.
Abstract: Background: Immunotherapy agents are used to treat advanced head and neck lesions. We aim to elucidate relationship between immunotherapy and surgical wound complications. Methods: Retrospective multi‐institutional case series evaluating patients undergoing ablative and flap reconstructive surgery and immunotherapy treatment. Main outcome: wound complications. Results: Eight‐two (62%) patients received preoperative therapy, 89 (67%) postoperative, and 33 (25%) in both settings. Forty‐one (31%) patients had recipient site complications, 12 (9%) had donor site. Nineteen (14%) had major recipient site complications, 22 (17%) had minor. There was no statistically significant difference in complications based on patient or tumor‐specific variables. Preoperative therapy alone demonstrated increased major complications (odds ratio [OR] 3.7, p = 0.04), and trend to more donor site complications (OR 7.4, p = 0.06), however treatment in both preoperative and postoperative therapy was not. Conclusions: Preoperative immunotherapy may be associated with increased wound complications. Controlled studies are necessary to delineate this association and potential risks of therapy.